Germany's Construction Industry: Stabilization on the Horizon - Bernd Bartholmai; Martin Gornig (Weekly Report, 2005)
The construction volume this year will reach a value of just under euro 230 billion _ a drop as compared to 2004 of close to 3%. At approximately 1.5%, the price increase should turn out somewhat higher than the previous year, which means the real construction volume will thus shrink by a good 4%. While the development during the first six months of this year was clearly on the decline, improved demand in the second half of the year makes a recovery likely. After many years of a downward trend, the construction industry could bottom out next year. Even if real construction of new buildings probably will not grow, at least the shrinking process is likely to come to an end. In particular commercial construction is a motor for growth.
Keywords: 330